2014
DOI: 10.1007/s11886-014-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Hormones, Metabolic Syndrome, and Diabetes in Men and Women

Abstract: Endogenous sex hormones predict impairments of glucose regulation. Cross-sectional studies suggest that lower levels of testosterone in men and higher levels in women increase risk of metabolic syndrome and diabetes, while lower levels of sex hormone binding globulin in both men and women increase risk of metabolic syndrome and diabetes. In a systematic review, we summarize existing longitudinal studies, which suggest similar patterns. However, these studies are often limited to a single sex steroid measure. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 73 publications
3
56
0
6
Order By: Relevance
“…Consistent with studies comparing persons with and without glucose perturbations (diabetes, IFG, IGT) (Selvin et al, 2007;Colangelo et al, 2009;Grossmann, 2011;Shin et al, 2012;Kim & Halter, 2014), we found weak evidence suggesting that pre-diabetic men had lower total testosterone levels than men without pre-diabetes. This observed inverse, but statistically non-significant, association was also seen when defining pre-diabetes based on IFG, IGT, and HbA1c.…”
Section: Androgenssupporting
confidence: 87%
“…Consistent with studies comparing persons with and without glucose perturbations (diabetes, IFG, IGT) (Selvin et al, 2007;Colangelo et al, 2009;Grossmann, 2011;Shin et al, 2012;Kim & Halter, 2014), we found weak evidence suggesting that pre-diabetic men had lower total testosterone levels than men without pre-diabetes. This observed inverse, but statistically non-significant, association was also seen when defining pre-diabetes based on IFG, IGT, and HbA1c.…”
Section: Androgenssupporting
confidence: 87%
“…However, it is also possible that unmeasured factors, such as earlier brain characteristics and/or common pathways (i.e., developmental, environmental, and/or genetic mechanisms), might have influenced both hormonal profiles and brain volumes in early adulthood and mid‐life and resulted in their observed associations. Given the involvement of sex hormone levels in several developmental and biological processes and given data indicating that they are often involved in bidirectional mechanisms (Allan & McLachlan, 2010; Kim & Halter, 2014), it is possible that their association with brain health is also bidirectional. Future studies are needed to establish the temporality of the association throughout the life‐course.…”
Section: Discussionmentioning
confidence: 99%
“…However, in examinations of conventional lipid profiles, greater androgenicity (as represented by higher testosterone [T], lower estradiol [E2], and lower sex hormone binding globulin [SHBG]) has been associated with more atherogenic profiles in women and less atherogenic profiles in men, and such associations are partially mediated and/or attenuated after adjustment for visceral and hepatic adiposity. 8 Therefore, we examined the relationships between endogenous sex hormone levels and lipoprotein subclasses using data from preliminary studies of the MASALA study, a cohort of Asian Indians in the United States. 9 The aim of this secondary analysis was to determine whether more androgenic profiles were associated with more atherogenic lipoprotein subfraction profiles in women and less atherogenic lipoprotein profiles in men and whether such associations persisted after consideration of adipose tissue mass.…”
Section: Introductionmentioning
confidence: 99%